Imaging of Hsp70-positive tumors with cmHsp70.1 antibody-conjugated gold nanoparticles - Gehrmann MK (Dove Medical Press, 2015)
Mathias K Gehrmann,1 Melanie A Kimm,2 Stefan Stangl,1 Thomas E Schmid,1 Peter B Noël,2 Ernst J Rummeny,2 Gabriele Multhoff11Department of Radiation Oncology, 2Department of Diagnostic and Interventional Radiology, Klinikum rechts der Isar, Technische Universität München, Munich, GermanyAbstract: Real-time imaging of small tumors is still one of the challenges in cancer diagnosis, prognosis, and monitoring of clinical outcome. Targeting novel biomarkers that are selectively expressed on a large variety of different tumors but not normal cells has the potential to improve the imaging capacity of existing methods such as computed tomography. Herein, we present a novel technique using cmHsp70.1 monoclonal antibody-conjugated spherical gold nanoparticles for quantification of the targeted uptake of gold nanoparticles into membrane Hsp70-positive tumor cells. Upon binding, cmHsp70.1-conjugated gold nanoparticles but not nanoparticles coupled to an isotype-matched IgG1 antibody or empty nanoparticles are rapidly taken up by highly malignant Hsp70 membrane-positive mouse tumor cells. After 24 hours, the cmHsp70.1-conjugated gold nanoparticles are found to be enriched in the perinuclear region. Specificity for membrane Hsp70 was shown by using an Hsp70 knockout tumor cell system. Toxic side effects of the cmHsp70.1-conjugated nanoparticles are not observed at a concentration of 1–10 µg/mL. Experiments are ongoing to evaluate whether cmHsp70.1 antibody-conjugated gold nanoparticles are suitable for the detection of membrane-Hsp70-positive tumors in vivo.Keywords: heat shock protein 70, tumor biomarker, theranostics, multimodal CT, multispectral CT, k-edge